Publications of B.J. van der Walt 1960-2010 - Bishop, S. (Koers, 2010)
At the Ferdinand Postma Library of the Potchefstroom Campus of the North-West University an electronic list (both chronological and alphabetical according to titles) of B.J. van der Walt’s publications from 1960 to 2000 is available. (To access the list, go to http://www4-win2.p.nwu.ac.za/dbtw-wpd/textbases/puk-eeu.htm and type in the author’s name: Van der Walt BJ) The website of Mr. Steve Bishop (www.allofliferedeemed.co.uk/ vanderwalt.htm) provides an annotated bibliography of all Van der Walt’s publications in English, as well as a list of the publications of the Institute for Reformational Studies. (E-mail: stevebishop.ukgmail.com)